Impact of spiritual practices on happiness in middle-agers - J.C.2, *Dr. (Mrs.) Purohit Anjana1, Dr. Ajawani (International Multidisciplinary Research Journal, 2011)
At every period of the life span, happiness is influenced by a number of factors. Success in a chosen vocation, which brings with it prestige, financial rewards, and improved social status for the family, goes a long way toward making middle-age a satisfying period of life for men. For women, whose lives have usually been centered around the home, satisfaction in middle-age depends mainly on the success with which they are able to adjust to the changes they must make in the home making role (Gorney & Cox, 1973). Spiritual practices, adopted and exercised by middle agers, also seem to have their say in happiness during middle-age. The authors intended to observe the impact of spiritual practices on happiness of male and female middle-agers. It has been hypothesized that middle-agers adopting spiritual practices would show higher level of happiness than non-adopting middle-agers and also would benefit more form spiritual practices. Thirty subjects were selected incidentally from four sub-groups i.e., high spiritual practicing males, low spiritual practicing males, high spiritual practicing females, and low spiritual practicing females, and were administered happiness scale.